The prevalence of suicidal behavior and its associated factors among wives with polygamy marriage living in Gedeo zone, southern Ethiopia, 2020. - Chalachew Kassaw (Public Library of Science (PLoS), 2021)
Introduction Polygamy is a trend of marriage characterized by having two and more wives or husbands at the same time. In low and middle-income countries including Ethiopia, polygamy has a significant negative effect on the social, economic, physical, and mental well-being of women. Therefore, this study aimed to assess the prevalence and associated factors of suicidal behavior among wives with polygamy marriage living in the Gedeo zone, Southern Ethiopia, 2020. Methods A community-based study employing cross-sectional design and systematic sampling technique was used to select wives with polygamy marriage who are residents of Gedeo Zone from November to December 2020. The World Health Organization Suicidal Behavior Questions (SBQ-5) was adapted to explore the outcome variable. The Logistic regression at 95% CI, p<0.05 was used to identify factors associated with suicidal behavior. Results This study enrolled 423 respondents. The study revealed that, the overall prevalence of suicidal behavior was 157(37%). Illiteracy, being a wife of a husband with three and more other wives, current history of depression, intimate partner violence, and poor social support were significantly associated with suicidal behavior at 95% confidence interval, p < 0.05. Conclusion This study found that one-third of the respondents had suicidal behavior. Different significant socio-demographic and psychosocial variables were identified. Thus, due attention should be given to minimize the practice and its effect on the mental wellbeing of a mother and their children.